The Impact of Pentagon's Fraud Elements on Predicting Financial Report Fraud - Yansyahid , Dzikrie; Indrastuti, Dewi Kurnia (Jurnal Akuntansi Bisnis Pelita Bangsa, 2023)
The present study aims to investigate the impact of fraudulent components within the Pentagon on its ability to predict the occurrence of financial report fraud. This research employs several independent variables, including financial targets, external pressure, liquidity, nature of the industry, audit opinion, proportion of independent commissioners, and a number of CEO photos, while the dependent variable is fraudulent financial reporting. This investigation employed data pertaining to manufacturing enterprises that were listed on the Indonesia Stock Exchange during the period spanning from 2018 to 2020. In this study, a total of 104 companies were sampled and a purposive sampling method was utilized to obtain 310 data points. The present investigation utilized a statistical tool known as multiple regression analysis. The findings of the present investigation demonstrate that both the financial target variables and the types of industries significantly adversely impact the occurrence of fraudulent financial reporting. Notably, the factors of external pressure, liquidity, audit opinion, the ratio of independent commissioners, and the quantity of CEO images appear to bear no influence on fraudulent financial reporting. Keywords: Fraud Pentagon, Fraudulent Financial Reporting, Financial Target